Development and validation of an educational information web page for family members with relatives in the Intensive Care Unit (ICU) - Abdul Halain, Azura; Tang, Li Yoong; Chong, Mei Chan; Ibrahim, Noor Airini; Lim Abdullah, Khatijah (Elsevier, 2022)
Aim This paper describes the development and validation of an educational information web page designed for family members who have relatives in the Intensive Care Unit (ICU).